2021
DOI: 10.14639/0392-100x-suppl.1-41-2021-02
|View full text |Cite
|
Sign up to set email alerts
|

Trattamento delle fistole rinoliquorali: quando è richiesto un approccio chirurgico multidisciplinare al basicranio?

Abstract: Cerebrospinal fluid (CSF) leak remains a rare condition, characterized by serious complications and potentially fatal. According to different etiologies, CSF leaks may be classified into two main categories: traumatic and spontaneous. Spontaneous fistulas seem to be mainly related to obesity and idiopathic intracranial hypertension. Diagnosis is both clinical and radiological. During the last three decades, surgical treatment has mostly shifted to endonasal endoscopic approach, which widely demonstrated to be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 50 publications
0
12
0
2
Order By: Relevance
“…Second, CSF leaks can appear spontaneously in relation to other conditions such as intracranial hypertension or CSF hypotension. [3] Spontaneous CSF fistulas are characterized by positional headache, where the headache improves in supine and worsens on sitting, related to the possible leptomeninges traction as well as nuchal rigidity, photophobia, diplopia, and even radiculopathy. e imaging diagnosis of this type of fistulae can be performed through a CT to locate the site of the bone defect; even though the patient has clear symptoms of a CSF leak, images may be normal so studies with MRI and CT myelography can be extended.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, CSF leaks can appear spontaneously in relation to other conditions such as intracranial hypertension or CSF hypotension. [3] Spontaneous CSF fistulas are characterized by positional headache, where the headache improves in supine and worsens on sitting, related to the possible leptomeninges traction as well as nuchal rigidity, photophobia, diplopia, and even radiculopathy. e imaging diagnosis of this type of fistulae can be performed through a CT to locate the site of the bone defect; even though the patient has clear symptoms of a CSF leak, images may be normal so studies with MRI and CT myelography can be extended.…”
Section: Discussionmentioning
confidence: 99%
“…Second, CSF leaks can appear spontaneously in relation to other conditions such as intracranial hypertension or CSF hypotension. [ 3 ]…”
Section: Discussionmentioning
confidence: 99%
“…The spontaneous group is further divided into high-pressure and low-pressure subgroups (according to CSF pressure). 3…”
Section: Diagnosis: Cerebrospinal Fluid Leakmentioning
confidence: 99%
“…In addition, screening for medication that can exacerbate IIH, including doxycycline, carbidopa, levodopa, cyclosporine, danazol, lithium, phenytoin, vitamin A, and some contraceptive drugs is also necessary. 3,4…”
Section: Diagnosis: Cerebrospinal Fluid Leakmentioning
confidence: 99%
“…The patient was placed in an erect 80-degree right anterior oblique position in front of a gamma camera, giving to drink 10 mL of water with 18.5 MBq (0.5 mCi) of 99m Tc-DTPA and recording sequential images (480 frames in 60 seconds) from the nose to the epigastric region. [2][3][4][5][6][7][8][9][10] The qualitative analysis of the images demonstrated that the sucking ability was preserved, but with a partial oral inability to contain the liquid bolus (A, early visualization of the oropharynx in the preswallowing phase); this event has to be referred to the oral incapability to contain the liquid bolus. Oropharynx swallowing phase showed irregular movements, probably due to a novel postsurgical anatomy as well as to a superior esophageal sphincter hypertonia.…”
mentioning
confidence: 99%